(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Drug-drug interaction (DDI) screening programmes aim to increase the safety of medication by issuing alerts based on the severity of DDIs, since an increased risk of adverse drug events has been reported for some DDIs (clinically relevant alerts). However, not all DDI alerts may be clinically relevant, depending on the clinical decision support system (CDSS) interaction tool used and the target population. There are few data about the frequency and relevance of DDIs in the paediatric population. The objective of this study was to evaluate the prevalence and appropriateness of high-risk DDI alerts (drug combinations that are rated as “contraindicated” or “contraindicated by precaution” according to the Swiss CDSS interaction tool Pharmavista® (HCI Solutions AG, Bern, Switzerland)) in paediatric inpatients. METHODS We carried out a retrospective, single-centre study examining a cohort of paediatric cases hospitalised between January and May 2017 on the surgery/orthopaedic and oncology wards at the University of Basel Children’s Hospital (UKBB), Switzerland. Drugs administered to the patients concomitantly were obtained from the medical records. DDI screening was performed using Pharmavista®. All DDIs detected were documented with their severity grading for each hospital day per case. The clinical relevance of DDI alerts for drug combinations rated as contraindicated or contraindicated by precaution was critically evaluated by a literature review. RESULTS A total of 300 patient cases were assessed for “contraindicated” or “contraindicated by precaution” DDI alerts. Of these, none had “contraindicated” and five had DDI alerts rated as “contraindicated by precaution” (1.7%, 95% CI 0.6–4.1%). The corresponding drug combinations were tramadol/fentanyl/morphine-nalbuphine (n = 3), droperidol-ondansetron (n = 1) and methotrexate-metamizole (n = 1), given for a duration of 1–2 days. Adverse drug events (ADEs) due to these three combinations (QT prolongation with the combination droperidol-ondansetron, reduced effect of opioid agonists with nalbuphine and increased haematotoxicity with methotrexate-metamizole) were not documented in the patients’ medical records. CONCLUSIONS The low prevalence of contraindicated DDIs suggests that Pharmavista® has a low risk of over-alerting when used in a Swiss paediatric hospital. However, the current literature suggests that the severity rating of established contraindicated DDIs could be partially downgraded, and that patient/population-specific evaluations of DDI alerts are needed.